2014
DOI: 10.1158/1535-7163.mct-14-0175
|View full text |Cite
|
Sign up to set email alerts
|

Human Umbilical Cord Blood–Derived Mesenchymal Stem Cells Producing IL15 Eradicate Established Pancreatic Tumor in Syngeneic Mice

Abstract: Mesenchymal stem cells (MSC) represent a new tool for delivery of therapeutic agents to cancer sites because of their strong tropism toward tumors. IL15 has demonstrated a potent antitumor activity in various animal models as well as clinical trials. However, because of its short half-life, effective therapeutic effects usually require a high dose, which often results in undesired side effects; thus, new strategies for overcoming this disadvantage are needed. In this study, human MSCs were isolated from umbili… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 42 publications
(52 reference statements)
1
37
0
1
Order By: Relevance
“…However, artificial fusion of MSCs with esophageal carcinoma cell line EC9706 resulted in hybrids with declined cell growth, increased apoptosis and suppressed tumorigenicity 31. UC-MSCs promote the proliferation of mouse pancreatic cancer cell line Pan02 in vivo , however, MSCs producing IL-15 eradicate established pancreatic tumors in syngeneic mice 32.…”
Section: Mscs In Anticancer Therapiesmentioning
confidence: 99%
“…However, artificial fusion of MSCs with esophageal carcinoma cell line EC9706 resulted in hybrids with declined cell growth, increased apoptosis and suppressed tumorigenicity 31. UC-MSCs promote the proliferation of mouse pancreatic cancer cell line Pan02 in vivo , however, MSCs producing IL-15 eradicate established pancreatic tumors in syngeneic mice 32.…”
Section: Mscs In Anticancer Therapiesmentioning
confidence: 99%
“…Additionally, it has been reported that umbilical cord MSCs with previously enhanced IL-15 gene expression significantly suppresses pancreatic tumor growth in mice. Moreover, in this study it has been demonstrated that MSCs, induced for IL-15 expression, stimulate accumulation of NK cells and CD8 + T lymphocytes, thus supporting antitumor immune response [133]. Also, it has been shown that IFN- β -producing MSCs from bone marrow [134], as well as adipose tissue [135], inhibit proliferation of hepatocellular carcinoma or breast cancer, respectively.…”
Section: Antitumor Features Of Mscsmentioning
confidence: 99%
“…(20,21) In our study, the UCBMSCs were preferred over the other stem cell types due to their unique advantages, such as painless collection procedure, easy availability, high efficiency of differentiation and faster self-renewal, with lower risk for graft versus host disease. (22) Studies by Sun et al (23) and Jing et al (24) showed that these cells, when transplanted into normal rat tissues, failed to produce tumours or any immune rejection response. Moreover, reports on the efficiency of UCBMSCs for the treatment of various injuries and diseases, both clinically and pre-clinically, have been documented in the recent past.…”
Section: Discussionmentioning
confidence: 99%